Pronunciation Errors of English Teachers in Teaching Storytelling: Phonetic Analysis - Siti Nurul Hapizah Damanik (Indonesian Postgraduate Foreign Language Education Association, 2024)
Pronunciation errors can significantly impact the clarity and comprehension of a story, leading to misunderstandings and reduced listener engagement. By emphasizing correct pronunciation, teachers enable clearer and more confident communication, significantly enhancing the effectiveness and impact of storytelling. This study aimed to investigate how English teachers use the International Phonetic Alphabet (IPA) during storytelling instruction to improve pronunciation accuracy. This study employed a descriptive-qualitative method. This research has been conducted through five English teachers using storytelling sessions with the same topic based on different YouTube video sources. The data will be collected through English teachers’ recordings when teaching storytelling. The data will be analyzed with IPA transcriptions to identify and categorize pronunciation errors in consonants, vowels, and diphthongs. The findings reveal a total of 36 pronunciation errors, including 18 vowel errors, 14 consonant errors, and 2 diphthong errors. The researcher suggests English teachers use the International Phonetic Alphabet (IPA) for teaching pronunciation, particularly in storytelling, to improve students' understanding of phonetic nuances, reduce pronunciation errors, and enhance communication and storytelling skills.